Sustainability as Cultural Paradigm - Senatore, Gianluca; Spera, Francesca (Richtmann Publishing, 2021)
In this work we have highlighted why sustainability should be analyzed as a cultural concept.The sociological analysis of the last decades on the social environmentalist movements has concentrated his attention on the reasons that pulled the activists on adopting pro-environmental behaviors. These analysis have always considered the reasons of the movements as actions moved by the fear of environmental crisis. This paper contributes on conducting an analysis on sustainability with a different approach based on new paradigms. Â Received: 2 May 2021 / Accepted: 15 June 2021 / Published: 8 July 2021